Johnson-Mehl-Avrami kinetics as a universal description of crystallization in glasses? - Svoboda, Roman (Elsevier Science, 2024)
Applicability of the Johnson-Mehl-Avrami (JMA) model beyond the typical range of the negative asymmetries of the crystallization peak was tested by means of theoretical simulations. Using the solid-state kinetic equation with implemented temperature dependences of either activation energy E or pre-exponential factor A, it was shown that the originally monotonically increasing transformation rate constant changes its evolution with temperature to a non-monotonous course, exhibiting a broad maximum. If the crystallization process following the non-isothermal JMA kinetics proceeds near this maximum, the asymmetry of the corresponding kinetic peak can gradually change to significantly positive values. Of particular interest are the cases with the JMA kinetic exponent mJMA >= 2, where the asymmetry of the JMA peaks changes with increasing heating rate from the typical negative values to largely positive values - such crystallization behavior was indeed observed for several chemically diverse materials (polymers, small organic molecules, chalcogenide and oxide glasses).
Johnson-Mehl-Avrami kinetika jako univerzální popis krystalizace ve skle?
Keywords: JMA model; Extended applicability; Theoretical simulation; Asymmetry; Johnson-Mehl-Avrami; kinetika; krystalizace; sklo